Disruption of Long-Term Effusive-Explosive Activity at Santiaguito, Guatemala - Lamb, Oliver D.; Lamur, Anthony; Díaz-Moreno, Alejandro; De Angelis, Silvio; Hornby, Adrian J.; von Aulock, Felix W.; Kendrick, Jackie E.; Wallace, Paul A.; Gottschämmer, Ellen; Rietbrock, Andreas; Alvarez, Isaac; Chigna, Gustavo; et al. (Frontiers in Earth Science, 2019)
A comprehensive understanding of the dynamic evolution of active volcanic systems requires extensive sets of geophysical and geological data to fully constrain and understand shifts in eruptive behavior. The Santiaguito dome complex, Guatemala, is a remarkable example of an open-vent volcanic system where continuous eruptive activity has historically been characterized by cycles of effusion and frequent, small to moderate, gas-and-ash explosions. During 2015-2016 the volcano experienced a rapid intensification of activity including large vulcanian explosions, frequently accompanied by pyroclastic density currents. Here we present a chronology of the eruptive activity at Santiaguito from November 2014 - May 2017, compiled from field observations (visual and thermal) and activity reports. We also present seismic and acoustic infrasound data collected during the same period, the longest and largest dataset collected at Santiaguito to date. Three major phases of eruptive activity took place during the study period. The first phase was consistent with the long-term eruptive behavior reported at Santiaguito by previous studies: lava effusion simultaneous with small (<1 km plume height), regular (25-200 minute intervals), gas-and-ash explosions. The second phase from July 2015 to September 2016 was defined by large (<5-7 km plume height) vulcanian explosions at irregular intervals and often accompanied by pyroclastic density currents. The third phase was marked by a return to effusive activity in October 2016 interspersed by small, gas-rich explosions. Over 6000 explosive events were recorded by seismic and infrasound during the study period and clearly delineate the three phases of activity at the volcano. Furthermore, we present the first documented geophysical evidence of explosion blast waves and volcano-tectonic earthquake swarms at Santiaguito. An important implication of observations is that negative trends in explosion rates at silicic lava dome eruptions cannot be used alone as an indicator of future weaker activity and reduced risk. The dataset introduced here will serve as the foundation for future studies of the long-lived effusive eruption and rapid transitions to explosive volcanic activity at Santiaguito dome complex.